Adolescents’ Internet addiction: Does it all begin with their environment? - Khansa Chemnad; Maryam Aziz; Azza O. Abdelmoneium; Sanaa Al-Harahsheh; Ahmed Baghdady; Fatima Y. Al Motawaa; Diana Alsayed Hassan; Raian Ali (Child and Adolescent Psychiatry and Mental Health, 2023)
Abstract Background This is one of the few studies that examines adolescent Internet addiction (IA) among Middle Eastern population. The purpose of this study is to determine whether adolescents’ family and school environments play a role in their Internet Addiction. Methods We conduced a survey that included 479 adolescents in Qatar. The survey collected demographic data, the Internet Addiction Diagnostic Questionnaire (IADQ), the Brief Family Relationship Scale (BFRS) and questions from the WHO Health Behavior in School-aged Children (HBSC) survey that assess school environment, academic performance, teacher support, and peer support of the adolescents. Factorial analysis, multiple regression, and logistic regression were used for statistical analysis. Results Family environment and school environment were negative and significant predictors of adolescent Internet addiction. The prevalence rate was 29.64%. Conclusion Results imply that interventions and digital parenting programs should not only target adolescents, but also include entities in the developmental environment of adolescents, i.e. their family and school.